2022
DOI: 10.1093/eurjpc/zwac056.020
|View full text |Cite
|
Sign up to set email alerts
|

SGLT2 inhibitors in heart failure with preserved and reduced ejection fraction: a systematic review and meta-analysis

Abstract: Funding Acknowledgements Type of funding sources: None. Background Over the recent months, the scenery of the pharmacological treatment of heart failure has changed. Sodium-glucose co-transporter 2 inhibitors (SGLT2i) have become the protagonists, as trial after trial is revealing a prognostic benefit of their use for patients with heart failure (HF). While their clear advantage in heart failure with reduced ejection fraction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
81
4
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(96 citation statements)
references
References 0 publications
9
81
4
2
Order By: Relevance
“…It has been estimated that 10-20% of people infected with SARS-CoV-2 develop long covid (2). With studies pointing to varying symptom clusters (3)(4)(5)(6), unclear pathogenesis (1,7), and a limited understanding of risk factors (8)(9)(10)(11), long covid remains enigmatic. In particular, it is still unclear how many previously infected suffer from long covid to such an extent that it is severely disruptive to daily living and quality of life, and in turn also disruptive to society (12).…”
Section: Introductionmentioning
confidence: 99%
“…It has been estimated that 10-20% of people infected with SARS-CoV-2 develop long covid (2). With studies pointing to varying symptom clusters (3)(4)(5)(6), unclear pathogenesis (1,7), and a limited understanding of risk factors (8)(9)(10)(11), long covid remains enigmatic. In particular, it is still unclear how many previously infected suffer from long covid to such an extent that it is severely disruptive to daily living and quality of life, and in turn also disruptive to society (12).…”
Section: Introductionmentioning
confidence: 99%
“…Other studies have also found females to be significantly more likely to report persistent neurocognitive symptoms following SARS-CoV2 infection. 21,[31][32][33][34][35] One study suggests that discrepancies in sex hormones related to inflammatory processes may also contribute to this difference we see in COVID-19 response. 36 The expression of angiotensin-converting enzyme-2 (ACE2) and transmembrane protease serine 2 (TMPRSS2) receptors, both of which are likely involved in COVID-19 pathogenesis, has also been suggested to differ between the sexes and may play a role in the long-term effects of COVID-19.…”
Section: Discussionmentioning
confidence: 95%
“…These same nociplastic pain mechanisms are also commonly superimposed on nociceptive pain states such as autoimmune disorders, where up one-third or more are thought to have what used to be called secondary FM and then more recently central sensitisation. The risk factors for these conditions include female sex (which has 1.5–2×OR), SES factors, poor sleep, physical inactivity and cigarette smoking, which overlaps a tremendous amount with what is seen in Long COVID 12 13. In the studies that have closely examined the postinfectious pain manifestations of both COVID and similar postinfectious syndromes, individuals who have pain preinfection are likely to be left with more chronic pain as one of the sequelae, although many develop de novo pain 14–17…”
Section: Parallels Between Fm and Long Covidmentioning
confidence: 99%